2021
DOI: 10.1097/scs.0000000000007820
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Subjective Comparisons of Split Thickness Skin Graft and Full Thickness Skin Graft for Radial Forearm Flap Donor Sites Using a New Measuring Method

Abstract: could infer meaningful results by reflecting the actual nasal dimensions in unilateral cleft lip patients.The 3D imaging analysis has become possible owing to recent advances in technology. Three-dimensional imaging systems have advantages of accuracy of image measurement, as well as limited distortion in image capture. Moreover, 3D surface data can be archived for the subsequent analysis, and the data is less influenced by subject's head position at the time of acquiring images. 2D photographs require several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 26 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Pain: Pain at the donor site was established as an essential outcome measure across six studies in our metaanalysis [10,11,[13][14][15][16]. Among these studies, Peter et al [13], Sidebottom et al [14], and Vahldieck et al [15] conducted quantitative assessments of pain, involving a total of 234 patients, and were thus included in the meta-analysis.…”
Section: Primary Outcome Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain: Pain at the donor site was established as an essential outcome measure across six studies in our metaanalysis [10,11,[13][14][15][16]. Among these studies, Peter et al [13], Sidebottom et al [14], and Vahldieck et al [15] conducted quantitative assessments of pain, involving a total of 234 patients, and were thus included in the meta-analysis.…”
Section: Primary Outcome Resultsmentioning
confidence: 99%
“…Eight studies were identified as eligible for inclusion in this study [9][10][11][12][13][14][15][16].…”
Section: Prisma: Preferred Reporting Items For Systematic Reviews And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Peters et al examined the use of an optical three-dimensional scanner to objectively evaluate defect volume at the donor site for STSG versus FTSG reconstruction. The authors found greater surface variation in patients undergoing STSG reconstruction, but no subjective differences in aesthetics – suggesting that patient-reported aesthetic measures are multifactorial [19 ▪▪ ]. Functionally, FTSG has had mixed results when compared to STSG.…”
Section: Skin Graftingmentioning
confidence: 93%
“…While full or split thickness skin graft is widely used to cover skin paddle defects, attempts with local ap and autologous fat transplantation have been tried, with favorable results [5,6,7]. Endoscopic-assisted pedicle dissection has been utilized to reduce linear scarring for harvesting vascular pedicle [8].…”
Section: Introductionmentioning
confidence: 99%